Development of Integration Systems using PLC Siemens S71200 and PLC OMRON CP1L-L20DR-A Based on Ethernet and KepServerEx - Lutfi, Lutfi; Muchtar, Taufik; Tri Budi Utami, Atikah (JEAT : Journal of Electrical Automation Technology, 2024)
This research aims to develop System Integration using Siemens S71200 PLC and OMRON CP1L-L20DR-A PLC based on Ethernet and KepServerEx. It is a deductive quantitative research employing an experimental method through several stages, starting from the literature study phase, system requirement analysis phase, and testing phase, both partially and in an integrated manner. The research was conducted at the Control and Automation Laboratory at ATI Makassar Polytechnic, spanning from July to September 2023. It is part of a laboratory research project involving four students as part of their final assignment. Research instruments utilized include Siemens S71200 AC/DC/RLY PLC trainer modules, OMRON CP1L-L20DR-A PLC trainer modules with CP1W CIF41, Switch, and a PC installed with TIA Portal, CX One (including CX Programmer and CX Server), KepServerEx, Aveva Intouch HMI, and Factory I/O applications. The research has successfully developed both in terms of protocol by utilizing advanced tag features in the KepServerEx application and in terms of HMI using Script features in the Aveva Intouch HMI application. Partial testing results regarding network aspects and OPC tag quality showed a 100% connection rate with Good data quality. Integrated testing results, both in terms of protocol and HMI, have also successfully integrated the devices from the Omron PLC to Factory I/O to Siemens PLC.